Pengaturan Kelompok Militan Dalam Konflik Bersenjata Menurut Hukum Humaniter Internasional - Wafiq Maulana Seknun; Arman Anwar; Welly Angela Riry (PATTIMURA Law Study Review, 2023)
ABSTRACT: Militants or so-called radical groups are groups of civilians whose purpose is to serve as a supplement to the regular military coup. The process of forming militants occured because of conflict between the Taliban and the Afganistan goverment which was supported by the United State so that insurgent groups were named militants or insurgent groups. The writing aims to find out the responsibility of militant groups as rebels who kill civilians in terms of international humanitarian law. The results of international Humanitarian Law research that regulates armed conflict between states and insurgents can be seen in article 3 of the 1949 Geneva Convention and Additional Protocol II of 1977. Subject of international law, both must comply with humanitarian law and are prohibited from committing acts that can be categorized as war crimes or crimes againts humanity. Responbility for rebel groups is the responsibility of the rebel commmand, but if it is carried out individually then it can be prosecuted individually in the national court and if the national court does not eforce the law againts the person concerned then it can be brought before the international Criminal Court it can accordance with the 1998 Rome Statute. Rebel groups the Taliban who are currently in power as well as other parties, are oliged to implement the 1949 Geneva Convention and aditional Protocol II both during armed conflict and in peacetime.